2015
DOI: 10.1007/s10637-015-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib treatment in Child–Pugh A and B patients with advanced hepatocellular carcinoma: safety, efficacy and prognostic factors

Abstract: It is possible that not only Child-Pugh score 5 and 6 but also 7 patients are eligible for future clinical trials with sorafenib or similar drugs. Various survival predictors identified in this study might be considered as stratification factor. Although both MVI and EHM is a phenotype of advanced HCC, MVI should be discriminated from EHM because of the prognostic impact on survival in sorafenib-treated advanced HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 29 publications
3
61
2
1
Order By: Relevance
“…With regard to cases in whom a response was not obtained, once sorafenib was introduced as a secondary treatment, and a more favorable prognosis was obtained as compared to the nontreatment group. At the time of discontinuation due to tumor progression or adverse events, in approximately 90% of cases, the Child-Pugh score was maintained at ≤7 points, and it was thought that overall, sorafenib introduction secondary to LFP treatment was possible [15]. In the present study, for secondary treatments following LFP, regardless of the maintenance of hepatic functional reserve, BSC was often selected.…”
Section: Discussionmentioning
confidence: 95%
“…With regard to cases in whom a response was not obtained, once sorafenib was introduced as a secondary treatment, and a more favorable prognosis was obtained as compared to the nontreatment group. At the time of discontinuation due to tumor progression or adverse events, in approximately 90% of cases, the Child-Pugh score was maintained at ≤7 points, and it was thought that overall, sorafenib introduction secondary to LFP treatment was possible [15]. In the present study, for secondary treatments following LFP, regardless of the maintenance of hepatic functional reserve, BSC was often selected.…”
Section: Discussionmentioning
confidence: 95%
“…This might be due to the difference in background liver such as chronic liver disease or normal liver [4,5]. On the other hand, HCV eradication could improve the hepatic functional reserve even for patients with Child-Pugh grade A liver cirrhosis and may have a favorable influence on the clinical outcome of patients with advanced HCC treated with sorafenib [16] ; however, these effects remain unclear. Therefore, in this study, we examined the impact of HCV eradication on the clinical outcome of patients with HCV-related advanced HCC treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Since the approval of sorafenib, studies have focused primarily on the safety and efficacy of this new molecular-targeted therapy in single-institution, clinical settings [5,13,14]. While these studies have each demonstrated clinical benefit in treating advanced HCC [5,13,14], others note the need to balance this opportunity with the potential for side effects and high treatment costs in the community setting [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While these studies have each demonstrated clinical benefit in treating advanced HCC [5,13,14], others note the need to balance this opportunity with the potential for side effects and high treatment costs in the community setting [15,16]. Specifically, treatment with sorafenib may cause a higher incidence of adverse drug reactions, such as hand-foot skin reactions, hypertension, and diarrhea, as well as an estimated USD 10,000-15,000/month in drug-related treatment costs [8,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%